1999
DOI: 10.1023/a:1024767020280
|View full text |Cite
|
Sign up to set email alerts
|

An examination of antecedent traumas and psychiatric comorbidity among male inmates with PTSD

Abstract: Despite substantially higher rates of posttraumatic stress disorder (PTSD) among male inmates than among men in the general population, there is a dearth of research on PTSD among incarcerated men. The current study addresses traumatic events that precede PTSD and psychiatric disorders that are comorbid with PTSD in an inmate sample. Seeing someone seriously injured or killed, being sexually abused, and being physically assaulted were the three most commonly reported antecedent traumas to PTSD. Lifetime and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
72
5
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 25 publications
11
72
5
3
Order By: Relevance
“…Sixteen percent reported having been neglected, 14% reported sexual abuse and 34-58% reported physical abuse (depending on the examination instrument). A similar result was reported by Gibson et al [8], with 68% of the inmates of a US penitentiary previously exposed to a traumatising situation.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Sixteen percent reported having been neglected, 14% reported sexual abuse and 34-58% reported physical abuse (depending on the examination instrument). A similar result was reported by Gibson et al [8], with 68% of the inmates of a US penitentiary previously exposed to a traumatising situation.…”
supporting
confidence: 87%
“…The prevalence of PTSD among offenders has less frequently and only recently been examined. However, these studies too found an increased prevalence of PTSD in delinquents [8,11,12]. It has been the aim of this analysis to check whether these results also apply to Switzerland.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Related results to mental disorders in the Iranian prisoners have shown that 75% of the under-survey population is affected by mental disorders, 2.32% by personality disorders (7) 78% by drug abuse, and 7.48% by mood disorders (8). The life style of such people involves greater exposure to harmful events, compared to the rest of the society (9,10). One of the ways to deal with accidents and damages is spirituality.…”
Section: Introductionmentioning
confidence: 99%